Critical thinking among fourth grade elementary students: a gender perspective - Kawuryan, Sekar Purbarini; Sayuti, Suminto A.; Aman, Aman (Jurnal Cakrawala Pendidikan, 2021)
Student intelligence in general is not distinguished by gender. However, some results of cognitive ability tests found these differences. The purpose of this study was to identify the critical thinking skills of fourth grade elementary school students based on gender. The critical thinking indicator refers to the Cornell Critical Thinking Test Level X. The selection of participants was carried out with consideration because the researcher had obtained permission from the principal of SDN Giwangan, parents, and had received approval from students so they were willing to be studied (convenience sampling). The sample consisted of 28 males and 17 females (N = 45). Data were analyzed using percentage, mean, standard deviation, range, and t-test. The findings show statistically significant differences in the mean critical thinking scores between male and female. The results of the study have implications for elementary school teachers who facilitate the learning process to develop critical thinking skills by applying different learning experiences. Teachers can follow up by considering differences in learning experiences based on the scope of the subject matter, the sequence of skills that are trained on students, and various choices of learning activities that develop critical thinking skills.